Chemical nature of active sites for defect‐mediated nucleation on silicon dioxide. Issue 2 (14th September 2015) - McCrate, Joseph M.; Ekerdt, John G.
Abstract : Germanium nanoparticle growth on SiO2 proceeds via defect‐mediated nucleation and particle density can be enhanced by chemically treating the SiO2 with SiHx . The influence of SiHx fragments on SiO2 surface sites is studied using a fluorescent probe‐based technique to understand the chemical nature of the inherent defect trapping sites and the chemical nature of the additional trapping sites formed by SiHx . Oxygen‐vacancy sites on SiO2 are the inherent sites for defect‐mediated nucleation. SiHx fragments, generated by cracking disilane on a hot tungsten filament, are shown to react with strained siloxane sites, leading to a conversion of these strained siloxane sites into a different low density defect site that is shown to display reactive characteristics similar to the oxygen‐vacancy defect sites. Previous work demonstrating an increased density of Ge nuclei on SiO2 surfaces with increasing SiHx exposure is interpreted in the context of the current experimental results. © 2015 American Institute of Chemical Engineers AIChE J, 62: 367–372, 2016